Viral vector‐mediated Cre recombinase expression in substantia nigra induces lesions of the nigrostriatal pathway associated with perturbations of dopamine‐related behaviors and hallmarks of programmed cell death. Issue 3 (27th March 2019) - Rezai Amin, Sara; Gruszczynski, Carole; Guiard, Bruno P.; Callebert, Jacques; Launay, Jean‐Marie; Louis, Franck; Betancur, Catalina; Vialou, Vincent; Gautron, Sophie
Abstract: Cre/loxP recombination is a widely used approach to study gene function in vivo, using mice models expressing the Cre recombinase under the control of specific promoters or through viral delivery of Cre‐expressing constructs. A profuse literature on transgenic mouse lines points out the deleterious effects of Cre expression in various cell types and tissues, presumably by acting on illegitimate loxP‐like sites present in the genome. However, most studies reporting the consequences of Cre‐lox gene invalidation often omit adequate controls to exclude the potential toxic effects of Cre, compromising the interpretation of data. In this study, we report the anatomical, neurochemical, and behavioral consequences in mice of adeno‐associated virus (AAV)‐mediated Cre expression in the dopaminergic nuclei substantia nigra, at commonly used viral titers (3 × 10 9 genome copies/0.3 μL or 2 × 10 9 genome copies/0.6 μL). We found that injecting AAV‐eGFP‐Cre into the SN engendered drastic and reproducible modifications of behavior, with increased basal locomotor activity as well as impaired locomotor response to cocaine compared to AAV‐eGFP‐injected controls. Cre expression in the SN induced a massive decrease in neuronal populations of both pars compacta and pars reticulata and dopamine depletion in the nigrostriatal pathway. This anatomical injury was associated with typical features of programmed cell death, including an increase in DNA break markers, evidence of apoptosis, and disrupted macroautophagy. These observations underscore the need for careful control of Cre toxicity in the brain and the reassessment of previous studies. In addition, our findings suggest that Cre‐mediated ablation may constitute an efficient tool to explore the function of specific cell populations and areas in the brain, and the impact of neurodegeneration in these populations. Abstract : Cre/loxP recombination is a widely used approach to study gene function in vivo, using mice models expressing the Cre recombinase under the control of specific promoters or through viral delivery of Cre‐expressing constructs. Our experiments show that AAV‐mediated Cre recombinase expression in the substantia nigra (SN) provokes lesions of the SN pars compacta and reticulata and perturbations of dopamine‐related behaviors by inducing DNA breakage, increased apoptosis, and perturbation of autophagy. These observations underscore the need for careful control of Cre toxicity when using this tool to study gene function in the brain.